Do open acces journal articles experience citation advantage? : A study in college - Sugiarto, Singgih; Widodo, Thomas Sixtus Iswahyudi Hari; Suyanto, Suyanto (Record and Library Journal, 2024)
Background of the study: Implementation open access (OA) have pushed journal articles become more visible and increase in citations of articles. Whether it is the general case for authors in all university?. Purpose: The aim of this study is to analyze the advantage of OA on numbers of citations of article journals published by authors from Universitas Surabaya, Indonesia. Method: The methods of analysis employed are descriptive analysis and independent sample t-test. Findings: The results showed three key findings, those are (1) the number of Scopus indexed OA articles at Universitas Surabaya is increased by 23% in 2022, (2) the majority of article publications are in OA journals, representing 70% of the 514 articles in question. (3) The t-test results indicated a significant difference with a value of t = 0.022 and a significance level of p < 0.05. Specifically, the number of citations was found to be higher in articles published in non-OA access journals than those in published in OA journals. Conclusion: The number of citations is not only affected by OA feature but also influenced by various factors, such as the reputation (quartile) of the journal, the scope of research collaboration, and the number of authors.